Meniscal bearing dislocation in unicompartmental knee arthroplasty: A not-so-uncommon twist in the joint - Tobias Bak Skov (Journal of Orthopaedic Reports)
Background: Knee osteoarthritis is a common cause of pain and disability, often necessitating knee arthroplasty in severe cases. Unicompartmental knee arthroplasty (UKA) is a well-established treatment for single-compartment osteoarthritis; however, meniscal bearing dislocation remains a frequent complication. Understanding the clinical presentation and management of this complication is increasingly important, given the growing use of UKA and the risk of functional impairment if diagnosis is delayed or the condition left untreated. Case presentation: A 63-year-old male presented with acute left knee pain and swelling following a minor incident. Physical examination revealed effusion and restricted range of motion. Radiographs confirmed meniscal bearing dislocation in the patient's UKA. Revision surgery at the patient's local hospital revealed extensive wear of the meniscal bearing, which was replaced. Following the procedure, the patient achieved full recovery, with restored knee mobility and resolution of pain. Conclusion: Meniscal bearing dislocation is a common complication of UKA. Diagnosis is confirmed through radiographs, and treatment depends on the severity of the dislocation and the condition of the patient and bearing. Preventing such complications requires attention to surgical technique, precise component fitting, and surgeon experience. Early recognition and appropriate revision surgery, as demonstrated in this case, can result in excellent outcomes.